THE INFLUENCE OF CAPTURE FISHERIES ZONES AFTER THE EXISTENCE OF LAW NO. 23 OF 2014 (STUDY AT ASAHAN DISTRICT FISHERIES SERVICE) - Emiel Salim Siregar; Indra Perdana Tanjung (Jurnal Ilmiah Advokasi, 2024)
ABSTRACTA capture fisheries zone is a sea area designated for special management and regulation to protect and maintain the fisheries resources within it. This concept includes strategies to limit fishing activities, implement sustainable fishing technology, and empower local communities to be involved in fisheries resource management. The influence of the capture fisheries zone in Asahan following Law No. 23 of 2014 in which the Asahan district fisheries service provides guidance, provides assistance to fishermen and socializes the capture fisheries zone twice a year to always remind the people of Asahan district about capture fisheries. These obstacles such as overfishing, illegal fishing, climate change and others require strong commitment and cooperation between regional governments, central government, local communities and other stakeholders. Counseling, active community involvement, increasing local capacity, as well as good and sustainable implementation of policies and regulations are the keys to overcoming these obstacles.Keywords:  Zone, Fisheries, Catch, Asahan Regency